PATIENT SERVICE AND SATISFACTION SYSTEMS - Abdul Haeba Ramli (Universitas Trisakti, 2016)
The objective the research is to analyze abo the influence of service delivery system to patient satisfaction. This analysis data used Structural Equation Modeling (SEM) to observe about interrelatedness between some variable. The population in this study is 225 persons of hospital medical patient in type C hospital in Makassar and spread to 75 hospital patients in Stella Maris hospital, 75 hospital patients in Akademis Jaury Yusuf Putra hospital, and 75 hospital patients in Grestelina hospital. The research result shows that service delivery system composed of physical support and contact personal are significant and positive influence on patient satisfaction